Melatih Kemampuan Membaca Menulis Dan Berhitung (Calistung) Serta Pengenalan Dasar Huruf Hijaiyah Untuk Siswa Pra-Sekolah Di Nagari Sicincin Tahun 2024 - Sitto Rahmana (CV. ITTC INDONESIA, 2024)
Community service with the theme Reading, Writing and Arithmetic Training as well as the introduction of hijaiyah letters is carried out in collaboration with the Nagari Sicincin community and related parties such as parents of students who are the objects of implementing the activities. The method used by families is direct face-to-face contact with pre-school students invited by the organizing committee. The material provided is an introduction to Latin letters and hijaiyah letters as well as an introduction to numbers followed by a series of simple calculations for pre-school students. The results of this service activity show success in mastering the material by the training participants. This can be seen from the high enthusiasm of the training participants in each training process.